How Do We End Sex-trafficking? A Day in the Life of Two Social Workers. Issue 2 (December 2019) - Henin, Bernard
This photo essay captures the grassroots work of Indian non-governmental organisation (NGO), Apne Aap Women Worldwide, to end sex-trafficking, in a nomadic community outside Delhi, where prostitution is passed down from mother-in-law to daughter-in-law. Young women are pushed into prostitution, after the birth of their first son. Their husbands and fathers-in-law are often the pimps. This nomadic group called the Perans and Saperas were labelled as Criminal Tribes under British colonialism and forced to give up their livelihood of making and selling dairy products, meat and indigenous medicine. Apne Aap social workers recruit girls to go to school, help them with homework, and try and make them stay in school, to break the cycle of inter-generational prostitution.